2006
DOI: 10.1080/03601230600857114
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Hot Pepper: Variation Among Accessions

Abstract: The U.S. Department of Agriculture (USDA) pepper (Capsicum spp.) germplasm collection contains several thousand members or accessions. Many of these species and cultivars have not been analyzed for their concentrations of ascorbic acid, capsaicin, and total phenolic compounds, which are important antioxidants having a number of benefits for human health. The objective of this investigation was to select candidate accessions of hot pepper having high concentrations of ascorbic acid, capsaicin, free sugars, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 14 publications
6
30
1
1
Order By: Relevance
“…They also have a significant role in traditional medicine (15,16). It has been reported that the red pepper fruit of Capsicum baccatum shows anti-inflammatory activity via nitric oxide scavenging activity (17). These findings indicate that the bell pepper has a potential immunosuppressive function through its effects on cells.…”
Section: Introductionmentioning
confidence: 50%
“…They also have a significant role in traditional medicine (15,16). It has been reported that the red pepper fruit of Capsicum baccatum shows anti-inflammatory activity via nitric oxide scavenging activity (17). These findings indicate that the bell pepper has a potential immunosuppressive function through its effects on cells.…”
Section: Introductionmentioning
confidence: 50%
“…The major active ingredients of RC are pungent capsaicinoids (capsaicin, dihydrocapsaincin), antioxidant vitamins (ascorbic acid, vitamin E), carotenoids (β-carotene, β-cryptoxanthine) and several organic acids and minerals (Antonious et al, 2006;Conforti et al, 2007), which are found to be significantly higher in RC compared with the green chilli of same species (Martinez et al, 2007;Conforti et al, 2007). Capsaicin, the primary pungent principle present in chillies, has been found to be effective in relieving diabetic and common neuropathic pains (Head, 2006;Ogata et al, 1996;Rashid et al, 2003), prevents adipocyte differentiation (Hwang et al, 2005), improves glucose tolerance and glucose stimulated insulin response (Gram et al, 2000a(Gram et al, , 2000b and reduces diabetic hyperglycemia (Tolan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…), se cultivan también como una fuente de nutrientes como carbohidratos, azúcares, calcio, magnesio, β-caroteno, ácido ascórbico, tocoferoles, las vitaminas A, C y E, y numerosos compuestos bioactivos no nutritivos como carotenoides y capsaicinoides, los cuales presentan actividad antioxidante importante (Antonious, Kochhar, Jarret, & Snyder, 2006;Singh et al, 2009;Topuz & Ozdemir, 2007).…”
Section: Introductionunclassified